H∞ loop-shaping controller designs for the single-phase UPS inverters. - Tzann-Shin Lee (IEEE Transactions on power electronics)
This paper proposes the H∞ loop-shaping approach to the designs of sinusoidal output voltage tracking controllers for single-phase UPS inverters. Selection of weighting functions is introduced, which is quite different from the case of step tracking. By modeling the uncertainty in load as plant output multiplicative perturbation, two H∞ loop-shaping control schemes that use only a capacitor voltage sensor are presented. The first design adopts a single-loop control scheme which has the advantage of simple control structure and easy implementation. But its transient performance and robustness are not satisfactory. The second controller with a dual-loop structure, additionally employing output of a capacitor current estimator as feedback, provides improved performance over the single-loop scheme and has the feature of low distortion, good regulating performance and insensitivity to the variation in load. Simulation and hardware experimental results, with comparison to the PI-based multiple feedback loop design, are given to validate the robustness property and regulating performance of the proposed controllers